Exponential Stability of Swelling Porous Elastic with a Viscoelastic Damping and Distributed Delay Term - Abdelbaki Choucha; Salah Mahmoud Boulaaras; Djamel Ouchenane; Bahri Belkacem Cherif; Mohamed Abdalla (Journal of Function Spaces)
In this paper, we consider a swelling porous elastic system with a viscoelastic damping and distributed delay terms in the second equation. The coupling gives new contributions to the theory associated with asymptotic behaviors of swelling porous elastic soils. The general decay result is established by the multiplier method.